(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to understand a profesional woman’s experience in facing the glass ceiling and the role of psychological capital in decision t transition into entrepreneurship. The study employed a qualitative method with a phenomenological approach, using in-depth interviews for data collection and the Miles and Huberman model for analysis data (data reduction, data display, and conclusion drawing). The findings are summarized into five main themes: glass ceiling, capabilities, meaning making of experience, psychological capital, and career transition. Overall, the study shows that career barriers and the way the experience is interpreted are connected to strengthened psychological capital, which supports the decision to transition into entrepreneurship as a career path perceived to be more suitable and more controllable.